Symptomatic hyperthyroidism in metastatic testicular mixed germ cell tumour. (8th June 2018) - Shah, Deep; Khalid, Nida
Abstract : This is a case of a young 34-year-old man who had symptomatic hyperthyroidism from an extremely high serum beta HCG level in the setting of a metastatic stage IIIC mixed germ cell tumour. The patient's thyroid function normalised with treatment of the cancer as the beta HCG levels declined.